Cut off Determination of Discrimination Indices in Differential Diagnosis between Iron Deficiency Anemia and β- Thalassemia Minor - Ebrahim Miri-Moghaddam; Narjes Sargolzaie (International Journal of Hematology-Oncology and Stem Cell Research, 2014)
Objective: The two most frequent hypochromic microcytic anemias are β- thalassemia minor (BTM) and iron deficiency anemia (IDA). Several discrimination indices have been proposed to quickly discriminate these similar entities via parameters obtained from automated blood count analyzers. The aim of this study to evaluate the diagnostic reliability of ten discrimination indices in the differentiation of Iron deficiency anemia (IDA) from β Thalassemia Minor (BTM). Methods: This study was conducted on 100 BTM and 70 cases with IDA in southern Iran. This evaluation was conducted through calculation sensitivity, specificity, positive and negative predictive value, Likelihood ratio positive, likelihood ratio negative and also we recalculated cut-off values for every formulas in our population and determination of Area Under Curve related to receiver operative characteristic (ROC) curves. Results: ROC for each discrimination indices show that, the highest diagnostic value based on the area under the ROC curve are related to the Green & King, England & Frazer and then Sirdah formulas (0.909, 0.907, 0.904, respectively) in South-east of Iran, and relatively different cut-off values for every formula. Conclusion: The spectrum β thalassemia mutations in each population can affect on various RBC indices, therefore, it is suggested to determine cut-off value for every formula in different populations.